Production, selection, characterizations and somatic embryogenesis of Malaysian salt-tolerant rice (Oryza sativa L. cv. MR219) through callogenesis - Kalhori, Nahid (2017)
Rice is one of the most important staple foods for human. However, millions hectares of land in the South and Southeast Asia were left uncultivated or grown with very low yields due to salinity. Therefore, the main objective of this study is to produce salt-tolerant Malaysia Indica rice cv. MR219) lines in vitro. The phenotypes, biochemical contents and seed germination capability of mother plant and salt-tolerant MR219 lines were compared. Firstly, MR219 callus was produced, then, callus was cultured separately on MS media supplemented with 2 mg/L 2,4-D and different concentration of NaCl (0, 50, 100, 200, and 300 mM NaCl) to produce salt-tolerant MR219 callus. Morphological comparison shows that MR219 callus from MS media yellowish color, soft, friable and nodular proliferating, however, callus produced in 100 mM NaCl are compact-type and blackish-brown and acutely-necrotic at 300 mM NaCl. Fresh and dry weight, water content, growth rate of MR219 callus and total protein content decreased as concentration of NaCl increased. On other hand, total proline content, total soluble sugar, lipid peroxidase and the activity of ascorbate peroxidase and catalase were increased. Histological analysis of salt-tolerant MR219 callus revealed that salinity negatively affected on development somatic embryos. Callus from 50 mM and 100 mM NaCl had been selected as salt-tolerant callus and was cultured on MS media supplemented with 2 mg/L kinetin and 1 mg/L BAP for shoot induction. Then, callus was subcultured in MS media supplemented with 0.5 mg/L BAP, 1 mg/L kinetin, 1 mg/L IBA and 0.5 mg/L NAA for root formation. At acclimatization stage, only MR219 plantlets from control (MS only) and 50 mM NaCl were survived and transferred to paddy soil. MR219 plantlets produced from 50 mM NaCl is called First generation (F1) salt-tolerant MR219. After 70 days, seeds of F1-salt-tolerant MR219 lines was successfully obtained. Following this, the grain characteristics of mother plant and F1-salt-tolerant MR219 lines were compared. Comparative study on phenotyes, leaves morphology, and root system found no variation between mother plant and second generation (F2)-salt-tolerant MR219 lines. Biochemical contents which are proline content, total soluble sugar and total protein showed no significant difference between mother plant and F2-salt-tolerant MR219 line. Seeds of F1-salt-tolerant MR219 was examined its germination capability in saline. Results found that seeds of F1-salt-tolerant MR219 able to germinate and growth in 50 mM and 100 mM NaCl. As conclusion, salt-tolerant MR219 rice was produced in vitro and have potential to be commercialized. The protocol to produce salt-tolerant rice can be used to produce other salt-tolerant plant.